Specific Missense Alleles of the Arabidopsis Jasmonic Acid Co-Receptor COI1 Regulate Innate Immune Receptor Accumulation and Function - He, Yijian (Public Library of Science, 2012)
Plants utilize proteins containing nucleotide binding site (NB) and leucine-rich repeat (LRR) domains as intracellular innate immune receptors to recognize pathogens and initiate defense responses. Since mis-activation of defense responses can lead to tissue damage and even developmental arrest, proper regulation of NB–LRR protein signaling is critical. RAR1, SGT1, and HSP90 act as regulatory chaperones of pre-activation NB–LRR steady-state proteins. We extended our analysis of mutants derived from a rar1 suppressor screen and present two allelic rar1 suppressor (rsp) mutations of Arabidopsis COI1. Like all other coi1 mutations, coi1(rsp) missense mutations impair Jasmonic Acid (JA) signaling resulting in JA–insensitivity. However, unlike previously identified coi1 alleles, both coi1(rsp) alleles lack a male sterile phenotype. The coi1(rsp) mutants express two sets of disease resistance phenotypes. The first, also observed in coi1-1 null allele, includes enhanced basal defense against the virulent bacterial pathogen Pto DC3000 and enhanced effector-triggered immunity (ETI) mediated by the NB–LRR RPM1 protein in both rar1 and wild-type backgrounds. These enhanced disease resistance phenotypes depend on the JA signaling function of COI1. Additionally, the coi1(rsp) mutants showed a unique inability to properly regulate RPM1 accumulation and HR, exhibited increased RPM1 levels in rar1, and weakened RPM1-mediated HR in RAR1. Importantly, there was no change in the steady-state levels or HR function of RPM1 in coi1-1. These results suggest that the coi1(rsp) proteins regulate NB–LRR protein accumulation independent of JA signaling. Based on the phenotypic similarities and genetic interactions among coi1(rsp), sgt1b, and hsp90.2(rsp) mutants, our data suggest that COI1 affects NB–LRR accumulation via two NB–LRR co-chaperones, SGT1b and HSP90. Together, our data demonstrate a role for COI1 in disease resistance independent of JA signaling and provide a molecular link between the JA and NB–LRR signaling pathways.